2011
DOI: 10.3109/07420528.2011.618959
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype and the Transition to College Life

Abstract: Social synchronizers of morningness-eveningness, or chronotype, begin to change during the developmental transition from adolescence to college life. The current study examined how these changes related to the sleep/wake patterns of 220 undergraduates (93 males/122 females) ranging in age from 18 to 29 yrs at a private university. Coping strategies students used to deal with early morning commitments and familial conflict over sleep patterns were also examined. Results revealed that evening chronotypes were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 36 publications
2
27
2
2
Order By: Relevance
“…The age-related shift to morningness is observed after controlling for demographic and socioeconomic factors, and correlates with most of the circadian functions with biological and behavioral circadian parameters (Klei et al, 2005;Monk et al, 2004;Mongrain et al, 2004;Taillard et al, 2011;Zimmermann, 2011). As subjects grow older, there is a tendency to go to bed and wake up earlier, and to present the highest levels of activation at an earlier time, and even more so from the age of 50 on.…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…The age-related shift to morningness is observed after controlling for demographic and socioeconomic factors, and correlates with most of the circadian functions with biological and behavioral circadian parameters (Klei et al, 2005;Monk et al, 2004;Mongrain et al, 2004;Taillard et al, 2011;Zimmermann, 2011). As subjects grow older, there is a tendency to go to bed and wake up earlier, and to present the highest levels of activation at an earlier time, and even more so from the age of 50 on.…”
Section: Agementioning
confidence: 99%
“…These results tend to be found in large samples that have used the MEQ. However, some studies have not found any gender differences (Paine et al, 2006;Zimmermann, 2011), and others reported ET was higher in females (Merikanto et al, 2012).…”
mentioning
confidence: 99%
“…A change in daily schedules allows for students to sleep longer in the morning, and to go to bed later in the evening without a need to decrease the amount of sleep (Zimmermann, 2011). This allows for evening-typed students to align their scheduling appropriately and comfortably with their sleep and wake patterns (Zimmermann, 2011).…”
mentioning
confidence: 99%
“…Upon beginning college, college students are faced with transferring from inflexible school schedules and parental restraint to increased flexibility in their schedules and a lack of dependence on parents (Zimmermann, 2011). A change in daily schedules allows for students to sleep longer in the morning, and to go to bed later in the evening without a need to decrease the amount of sleep (Zimmermann, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation